Protective effects and mechanisms of ellagic acid on intestinal injury in piglets infected with porcine epidemic diarrhea virus - Song, Zhuan; Deng, Cuifang; Chen, Qinyin; Zhao, Shengnan; Li, Peng; Wu, Tao; Hou, Yongqing; Yi, Dan (Frontiers in Immunology, 2024)
The present study was conducted to decipher the protection effects of ellagic acid (EA) on piglets infected with porcine epidemic diarrhea virus (PEDV). Thirty 7-day-old piglets were randomly assigned to three treatment groups: control, PEDV, and EA + PEDV groups. After a 3-day period of adaption, piglets in the EA + PEDV group were orally administered with 20 mg/kg·BW EA during days 4-11 of the trial. On day 8, piglets were orally administered with PEDV at a dose of 106 TCID50 (50% tissue culture infectious dose) per pig. Additionally, intestinal porcine epithelial (IPEC-1) cells infected with PEDV were used to investigate the anti-PEDV effect of EA in vitro. The results showed that EA at a dose of 10-40 μmol/L increased the viability of PEDV-infected IPEC-1 cells, and EA administration mitigated intestinal edema in piglets challenged with PEDV. Further studies indicated that EA treatment significantly increased the proportion of white blood cells in blood and concentrations of IL-6, IL-1β, and IL-10 in the serum, but decreased the TNF-α content and gene expression of IL-6, IL-1β, TNF-α, and CXCL2 in the jejunum. Moreover, EA intervention considerably elevated the activity of total superoxide dismutase (T-SOD), but decreased the H2O2 concentration in the ileum of piglets. Importantly, EA suppressed the increased expression of antiviral-related genes and proteins (including MXI, ISG15, HSP70, and p-IRF7) induced by PEDV challenge in the jejunum. Furthermore, PEDV infection increased the protein abundance of p-JAK2 and p-STAT3, which were further enhanced by EA supplementation. In conclusion, our results revealed that EA could promote the restoration of intestinal homeostasis by regulating the interferon pathway that was interrelated with the activation of JAK2/STAT3 signaling. These findings provide theoretical basis for the use of EA as a therapy targeting PEDV infection in piglets.